ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN VIDEO ANIMASI TERHADAP PEMAHAMAN KONSEP PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Pebrianty, Dilla; Fitriyani, Yani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of using animated video learning media to improve students' conceptual understanding in Natural and Social Sciences (IPAS) subjects in grade IV of SDN 2 Babakanreuma. The background of this study is based on the low level of students' conceptual understanding in IPAS learning, which is indicated by the low level of student involvement in the learning process. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation, and are analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that the application of animated video media in the learning process can significantly improve students' conceptual understanding. Animated videos are able to attract attention, increase enthusiasm for learning, and help students in several learning materials with everyday life. The main supporting factors in the successful use of this media include the support of innovative and creative learning methods, a supportive learning environment, and technology and learning resources. Thus, animated video media can be used as an alternative strategy in improving the effectiveness of IPAS learning at the elementary school level.